Using an Atlantis model of the southern Benguela to explore the response of ecosystem indicators for fisheries management. (July 2015) - Smith, Michael D.; Fulton, Elizabeth A.; Day, Robert W.
Abstract: Atlantis is a whole-of-system modelling framework developed for Management Strategy Evaluation. This paper describes an Atlantis model that was built to simulate the southern Benguela ecosystem and its major associated fisheries to assist fisheries management in the region. We divided the region into spatial zones based on hydrodynamics, current fishing management, and important ecosystem processes. We divided the biological components of the system into functional groups based on trophic interaction, life history traits and fisheries management objectives. We evaluated the model against historical data and known ecosystem interactions (such as competition and predation), and found that it simulates important ecological processes well at multiple trophic levels. We tested the model under fishing pressure scenarios and evaluated the performance of common ecosystem-level indicators. The response of the modelled system (as shown by indicators) was in line with expected behaviour of the indicators, reinforcing our confidence in the usefulness of the model. Highlights: The Atlantis modelling framework has been successfully applied to the southern Benguela ecosystem. The modelled system responds to forcing in ways that reflect observations and understanding of the real-world system. Ecosystem indicators in the model exhibit behaviour in line with expectations from real-world studies.